2020
DOI: 10.1016/j.shaw.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screen as a Predictor of Occupational Injury Among Denver Firefighters

Abstract: Background The Functional Movement Screen (FMS™) is a screening tool used to assess an individual's ability to perform fundamental movements that are necessary to do physically active tasks. The purpose of this study was to assess the ability of FMS to predict occupational injury among Denver Fire Department firefighters. Method FMS tests were administered from 2012 to 2016. Claim status was defined as any claim occurrence vs. no claim and an overexertion vs. no claim/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Their responsibilities were different from those in charge of apprehending offenders. A study conducted in the United States exploring the association between FMS score and a worker’s compensation claim found that the FMS did not predict future occupational injuries among Denver Fire Department firefighters [ 18 ]. All injuries caused by sports are categorized as sports injuries, including injuries produced because of work activities during working hours that meet the identification standard, namely, occupational injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Their responsibilities were different from those in charge of apprehending offenders. A study conducted in the United States exploring the association between FMS score and a worker’s compensation claim found that the FMS did not predict future occupational injuries among Denver Fire Department firefighters [ 18 ]. All injuries caused by sports are categorized as sports injuries, including injuries produced because of work activities during working hours that meet the identification standard, namely, occupational injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Purpose: This example exhibits the regular correlative beat of the scapular-thoracic area, thoracic spine and rib confine during corresponding furthest point shoulder movements. This likewise watches two-sided shoulder scope of movement, consolidating expansion, inward turn and adduction in one limit, and flexion, outside pivot, and snatching of the other (Shore, E., et al (2020). In this test 0 players get 0 score, 1 player get 1 score, 8 players get 2 scores and 1 player get 3 score as shown in figure1-4.…”
Section: ____________________________________________________________mentioning
confidence: 94%
“…Injury is a significant concern within first responder and military populations (2,17,20). The Functional Movement Screen (FMS) is commonly used to identify compensations when performing 7 specific movement patterns (deep squat [DS], hurdle step [HS], inline lunge [ILL], shoulder mobility [SM], active straight leg raise [ASLR], trunk stability push-up [PU], and rotary stability [RS]) (5,6).…”
Section: Introductionmentioning
confidence: 99%